Risk Aversion and Son Preference: Experimental Evidence from Chinese Twin Parents - Soo Hong Chew; Junjian Yi; Junsen Zhang; Songfa Zhong (Institute of Labor Economics (IZA), 2017)
We study the role of risk aversion underlying son preference in patriarchal societies, where sons serve as better insurance for old-age support than daughters. The implications of an insurance motive on son preference are two-fold. First, prior to the birth of their children, more risk-averse parents have a stronger preference for sons than for daughters. Second, after the birth of their children, parents with sons are more risk seeking, compared to parents with daughters. We adopt a within-twin-pair fixed-effects estimator with a weak identification assumption, which enables us to jointly identify these two effects. We further conduct an incentivized choice experiment to assess parental risk attitude in a sample of Chinese twins with children, and follow up with a second twin sample to examine the replicability of the findings. In both samples, we find that parents with greater risk aversion before the birth of their children are more likely to have sons through sex selection than parents with less risk aversion. Additionally, having sons significantly decreases parental risk aversion. These results contribute to the literature on the sources of son preference and help shed light on the nature of gender inequality.
Keywords: C93; D01; D80; J13; 330; risk aversion; son preference; twins; experimental economics